Classroom Management In English Teaching Learning Process: A Micro Ethnography Study At Al Jabar Elementary School Gondang, Sragen - Parmin, Parmin, Prof. Dr. Endang Fauziati, M. Hum, Dr. Phil. Dewi Candraningrum, M.Ed (2014)
The objective of this research is to investigate the classroom management in English teaching learning process at Al Jabar Elementary School. The problem appears at Al Jabar Elementary School is that as it is a new build school, it has many students and has to apply integrated curriculum. The classroom management in this study covers classroom organization, material and equipment, and how to discipline the students. The classroom organization includes: The rule and procedures, the classroom design, classroom environments, lesson plan, describing the material and equipment consists: the notion of material and equipment, the materials includes: subject matter, its presentation, difficuly task, clarity presentation, marking assignment, equipments; and describeing the discipline and consequences the students The study is conducted through a micro ethnographic design. The research findings show that the classroom management in English teaching learning process at Al Jabar Elementary School runs effectively and efficiently. The classroom is organized through well-planned rules and procedures, good environment, and lesson planning. The material and equipment prepared by the teacher are suited with the student's needs. In order to manage the students' behavior during the teaching learning process, the teacher applies reward and punishment to discipline the students. An important classroom management is identifying the behaviors match the condition, selecting a consequence, and delivering consequences for the behavior observed.